X^3 + 27 = 0
subtract 27 from both sides
X^3 = -27
take cubic root of both sides
X = -3 (this sentence is true for x = -3)
x3 + 27 = 0 the left side is the sum of the cubes, so it is factorable such as:
x3 + 33 = 0
(x + 3)(x2 - 3x + 9) = 0
Chat with our AI personalities
(c + 3)(c^2 - 3c + 9)
(x + 3)(x^2 - 3x + 9)
t3-1/27
3 cube =27 4 cube =64 5 cube =125 6cube=216 so 3 cubed + 4 cubed + 5 cubed = 6 cubed
2a^3 + 54 can first be factored into 2 (a^3 + 27). This can then be factored out to 2 (a + 3) (a^2 - 3a + 9).